Building information modelling: A case study approach to identify readiness criteria for process requirement - Ahmad Tarmizi, Haron; A., Marshall-Ponting; Mohd Nasrun, Mohd Nawi; Mohd Harris, Ismail (AENSI Publisher, 2014)
Building Information Modelling (BIM) is defined as an approach to building design and construction through modeling technology, associated set of processes and people to produce, communicate and analyse building information models. Although the potential benefits of BIM are well documented, the implementation process requires a thoughtful review of many aspects to realise those benefits. Case study of BIM implementation is therefore important to be carried out to understand the BIM nature and the context of its implementation to which suits the local needs. The aim of this paper is therefore set to present the BIM implementation case study in which focus on BIM readiness criteria. It is important to note that, the term BIM readiness criteria used within this paper, refers to the BIM implementation requirement that focus on process element that takes place at the organisational level. Setting in the background of Malaysian construction industry the research engaged a multiple-case-studies approach and four design consultant companies were selected for the primary data collection. Data from each company were analysed by using content analysis technique. This paper, however presents one of the case studies that was conducted at Industrialised Building System (IBS) company. Three readiness criteria were identified and they are Policy, Implementation Management and Process Change Strategy.